The Upaniṣads
1 online resource (xii, 439 pages)
Keywords: The Upaniṣads are among the most sacred foundational scriptures in the Hindu religion. Composed from 800 BCE onwards and making up part of the larger Vedic corpus, they offer the reader "knowledge lessons" on life, death, and immortality. While they are essential to understanding Hinduism and Asian religions more generally, their complexities make them almost impenetrable to anyone but serious scholars of Sanskrit and ancient Indian culture. This book is divided into five parts: Composition, authorship, and transmission of the Upaniṣads; The historical, cultural, and religious background of the Upaniṣads; Religion and philosophy in the Upaniṣads; The classical Upaniṣads; The later Upaniṣads. The chapters cover critical issues such as the origins of the Upaniṣads, authorship, and redaction, as well as exploring the broad religious and philosophical themes within the texts. The guide analyzes each of the Upaniṣads separately, unpacking their contextual relevance and explaining difficult terms and concepts. The Upaniṣads: A Complete Guide is a unique and valuable reference source for undergraduate religious studies, history, and philosophy students and researchers who want to learn more about these foundational sacred texts and the religious lessons in the Hindu tradition.